Comparative Performance of Biorational and Chemical Products for the Management of Bacterial Blight on Lilac - Cansu Oksel; Christina Jennings; Prabha Liyanapathirenage; Madhav Parajuli; Kumuditha D. Hikkaduwa Epa Liyanage; Terri Simmons; Fulya Baysal-Gurel (HortScience)
Bacterial blight caused by Pseudomonas syringae pv. syringae is a common disease of lilac (Syringa reticulata L.). This bacterium spreads plant to plant via insect vectors, wind, rain, and contaminated tools; hence, managing this disease is challenging. This study reports the efficacy of biological and chemical products for managing bacterial blight on lilac ‘Ivory Silk’. All plants except the noninoculated, nontreated control plants were spray inoculated with P. syringae pv. syringae strain FBG0464 (108 cfu·mL−1). Pydiflumetofen 6.9% + difenoconazole 11.5% (Postiva), thyme oil [Proud 3 (5.56%) and Tril-21 (15.5%) (preventive application)] and Bacillus amyloliquefaciens F272 (Stargus) were applied preventively 3 days before bacterial inoculation. Copper octanoate (Camelot O) (curative application) treatment was applied on the same day as the bacterial inoculation. Didecyl dimethyl ammonium chloride (KleenGrow) and thyme oil [Tril-21 (15.5%) (curative application)] were applied 7 days after inoculation. The plants were assessed weekly for bacterial blight, defoliation, and phytotoxicity. The experiments were conducted in 2021, 2022, and 2023. The final mean disease severity on inoculated, nontreated plants was 22.0%, 63.8%, and 64.0% in 2021, 2022, and 2023, respectively. All treatments significantly reduced bacterial blight compared with the inoculated, nontreated control. In 2021, plants treated with pydiflumetofen 6.9% + difenoconazole 11.5%, B. amyloliquefaciens F272 and thyme oil [Proud 3 (5.56%) and Tril-21 (15.5% as curative application)] had significantly lower bacterial blight severity compared with the rest of the treatments. In 2022, there were no significant differences in disease severity among the treatments. In 2023, plants treated with copper octanoate had the lowest disease severity. There was no phytotoxicity or defoliation in any of the treated plants. These findings can aid in developing suitable solutions for controlling bacterial blight caused by P. syringae pv. syringae on lilac.